STUDI TINGKAT KESEGARAN JASMANI SISWA KELAS V SMPN 5 KOPAH KECAMATAN KUANTAN TENGAH - Zainal Abidin; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Background of the problems in this study was the variation of physical activity undertaken by students of SMPN 5 kopah, many types of activities will be related to physical fitness. However, lack of accurate data on students of SMPN 5 kopah makes researchers intersted to conduct this research. This research is descriptive, objective of this study was to determine the physical fitness of class V students at SMPN 5 Kopah District of Kuantan Tengah. Data obtained from the test results TKJI with a sample of 26 male students (purposive sampling). Based on the analysis of physical fitness of class V students at SMPN5 Kopah District of Kuantan Tengah, it is obtained: 1) To Level Physical Freshness fitness of class V students at SMPN5 Kopah District of Kuantan Tengah to both categories once and either no or 0%, 2) To Level Physical freshness fitness of class V students at SMPN5 Kopah District of Kuantan Tengah with category showed 11.5% with the number of students as much as 3, 3) to Level Physical freshness fitness of class V students at SMPN5 Kopah District of Kuantan Tengah with less category showed 69.2% with the number of students as many as 18 people, and 4) to Level Physical Freshness fitness of class V students at SMPN5 Kopah District of Kuantan Tengah with less category once showed 19.2% with the number of students as many as five people. From the above data it can be concluded that the physical fitness level of class V students at SMPN5 Kopah District of Kuantan Tengah classified in categories less, it is known from the value of the average value of 11:08 with less category as they are the sum of the values 10-13..Keywords : Studies, Physical Fitnees,